Large-Amplitude Mountain Wave Breaking over Greenland - Doyle, James D.; Shapiro, Melvyn A.; Jiang, Qingfang; Bartels, Diana L. (2005)
A large-amplitude mountain wave generated by strong southwesterly flow over southern Greenland was observed during the Fronts and Atlantic Storm-Track Experiment (FASTEX) on 29 January 1997 by the NOAA G-IV research aircraft. Dropwindsondes deployed every 50 km and flight level data depict a vertically propagating large-amplitude wave with deep convectively unstable layers, potential temperature perturbations of 25 K that deformed the tropopause and lower stratosphere, and a vertical velocity maximum of nearly 10 m s1 in the stratosphere. The wave breaking was associated with a large vertical flux of horizontal momentum and dominated by quasi-isotropic turbulence. The Coupled Ocean?Atmosphere Mesoscale Prediction System (COAMPS) nonhydrostatic model with four-nested grid meshes with a minimum resolution of 1.7 km accurately simulates the amplitude, location, and timing of the mountain wave and turbulent breakdown. Finescale low-velocity plumes that resemble wakelike structures emanate from highly dissipative turbulent regions of wave breaking in the lower stratosphere. Idealized adiabatic threedimensional simulations suggest that steep terrain slopes increase the effective Rossby number of the relatively wide Greenland plateau, decrease the sensitivity of the wave characteristics to rotation, and ultimately increase the tendency for wave breaking. Linear theory and idealized simulations indicate that diabatic cooling within the boundary layer above the Greenland ice sheet augments the effective mountain height and increases the wave amplitude and potential for wave breaking for relatively wide obstacles such as Greenland. Published in Journal of the Atmospheric Sciences, v62 p3106-3126, September 2005.